Tingkat Upah, Inflasi dan Pengangguran: Aplikasi Model Lucas-Rapping terhadap Pasar Tenaga Kerja Indonesia Tahun 1960-2001 - Wicaksono, Teguh Yudo (UI Scholars Hub, 2002)
Lucas-Rapping model is considered as succesfull model to explain the labor force in America. We are apply this model on Indonesian case to analyze the fluctuation of labor force and to know wether the shift on labor supply and unemployment is a function of current real wage or not. We also intend to analyze behaviour of household to respond the real wage change. From demand side, we can trace out how deep the eduaction role on labor force quality. The conclusion may be helpfull on determining appropriate policy on education sector. We use data from BPS including lndikator Ekonomi dan Keuangan, Statistik Ketenagakerjaan (Sakernas), Keadaan Pekerja/Karyawan di Indonesia, Survei Sosial dan Ekonomi Nasional (SUSENAS) or Survei Penduduk Nasional (Supas). The rest of data is collected from internasional sources such as Summers Heston: PennWorld Table, data Barro and Lee and data Bank Dunia.